Peningkatan Kemampuan Motorik Halus Melalui Kegiatan Kolase Menggunakan Kapas di Kelompok B Ra Al Hidayah - Uswatun Hasanah; Vera Yuliani; Uswatur Rohmah; Vera Siti Magfiroh; Vera Oktafia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve children's fine motor skills through collage activities using cotton in group B RA Al Hidayah. Fine motor skills are an important aspect in early childhood development, which involves the coordination of small muscles to support various activities, such as writing, cutting, and drawing. The research method used is classroom action research (CAR) which is carried out in two cycles, with each cycle including the planning, implementation, observation, and reflection stages. The subjects of this study were 15 children in group B at RA Al Hidayah. Data collection techniques were carried out through observation, documentation, and interviews. The results of the study showed a significant increase in children's fine motor skills after participating in collage activities using cotton. Children became more skilled in controlling finger movements, tearing, sticking, and arranging cotton according to the given pattern. In addition, collage activities also increased children's creativity and concentration in completing tasks. The conclusion of this study is that collage activities using cotton media can be an effective strategy for developing fine motor skills in early childhood. The recommendation given is for teachers to integrate collage activities more often in learning, and to utilize various simple materials that are easy to find to stimulate optimal fine motor development.